Long-term effects of the war in Ukraine on its ecology and agriculture - Harkavenko, Iryna; Nikitenko, Olga (My University, 2024)
The war in Ukraine has had profound impacts on its ecology and agriculture, with significant consequences for the environment and food security. The conflict has caused extensive environmental damage, including pollution of rivers and lakes, chemical contamination of air, water and soil, destruction of forests, and rendering large areas of agricultural land unusable due to shelling and landmines. These bring out the urgent need for environmental recovery efforts and sustainable agricultural practices in Ukraine to mitigate the long-lasting effects of the war on its ecology and agriculture.

Війна в Україні серйозно вплинула на її екологію та сільське господарство, зі значними наслідками для довкілля та продовольчої безпеки. Конфлікт завдав великої шкоди навколишньому середовищу, включаючи забруднення річок і озер, хімічне забруднення повітря, води та ґрунту, знищення лісів і приведення великих площ сільськогосподарських угідь у непридатність через обстріли та мінування. Все це зумовлює гостру необхідність у відновленні навколишнього середовища та сталих методах ведення сільського господарства в Україні, щоб пом’якшити довготривалі наслідки війни для її екології та сільського господарства.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; war in Ukraine; environmental damage; pollution; agriculture; food security; війна в Україні; шкода навколишньому середовищу; забруднення; сільське господарство; продовольча безпека